Swearing-in Ceremony for Gary Austin (Superior Court) and Herbert Levy (Municipal Court) - Watkins, Howard::::::::: (1988)
Front row: Justices James Ardaiz and Hollis Best, Fresno County Bar Association President Dana French, Superior Court Judges Leonard Meyers and Blaine Pettitt, Municipal Court Judges Robert Mardikian and Annette LaRue